The Pied Piper of Hamelin (New Delhi, India Sterling)
Robert Browning's famous verse retelling of the medieval legend of the Pied Piper is renowned for its humor and vivid wordplay. When the selfish townspeople of Hamelin refuse to pay the piper for spiriting away the hordes of rats that had plagued them, he exacts his revenge by luring away their greatest treasure, the children of the town
English Stories
Keywords: English stories